5-HT 2 receptor mediates high-fat diet-induced hepatic steatosis and very low density lipoprotein overproduction in rats. (January 2018) - Li, Xin; Guo, Keke; Li, Tao; Ma, Shaoxin; An, Shanshan; Wang, Shanshan; Di, Jiao; He, Siyu; Fu, Jihua
Summary: Background: 5-HT has been shown to mediate abnormality of hepatic lipid metabolism through activation of mammalian target of rapamycin (mTOR). However, it is unclear whether 5-HT is directly involved in high-fat diet (HFD)-induced hepatic steatosis. Materials and methods: Male rats were allocated into seven groups with control, either HFD feeding, 5-HT treatment, or HFD feeding and 5-HT treatment with or without sarpogrelate treatment, all of which were executed for 4 weeks. HepG2 cells were exposed to 5-HT or palmitic acid (PA) with or without rapamycin or Sar treatment. Results: Rats fed with HFD or exposed to 5-HT led to abnormalities with activated hepatic mTOR-S6K pathway, overproduction of hepatic triglycerides and VLDL with steatosis, and hyperlipidemia, which were exacerbated by a combination of HFD and 5-HT. Sarpogrelate significantly inhibited above abnormalities induced by HFD and 5-HT, alone or in a combination. Additionally, HFD caused up-regulation of 5-HT2 receptors (5-HT2 R), including 5-HT2A R and 5-HT2B R, and 5-HT synthesis in the liver, without obvious influence on other 5-HT receptors gene expression. In HepG2 cells, both PA and 5-HT induced overproduction of triglycerides and VLDL with lipid droplets, and PA up-regulated 5-HT2A R and 5-HT2B R expression and 5-HT synthesis as well. Rapamycin fully abolished PA or 5-HT-induced mTOR activation, which was more effective than sarpogrelate. However, the inhibitory effects of rapamycin on PA or 5-HT-induced overproduction of triglycerides and VLDL were less than sarpogrelate. Conclusions: Up-regulation of hepatic 5-HT2 R and 5-HT synthesis by HFD is crucial for HFD-induced overproduction of hepatic triglycerides and VLDL with hyperlipidemia.